Interleukin-2 and STAT5 in regulatory T cell development and function - Mahmud, Shawn A. (Landes Bioscience, 2013)
Interleukin-2 and its downstream target STAT5 have effects on many aspects of immune function. This has been perhaps best documented in regulatory T cells. In this review we summarize the initial findings supporting a role for IL2 and STAT5 in regulatory T cell development and outline more recent studies describing how this critical signaling pathway entrains regulatory T cell differentiation and affects regulatory T cell function.